El aporte del profesional de la Contaduría Pública contra la evasión de impuestos. (2022)
This project is due to the research development at the particular initiative of the authors, entitled the contribution of the public accounting professional against tax evasion . This academic exercise was based on three specific objectives; determine the type of responsibility that the Publi c Accounting professional has against tax evasion, identify what type of tax evasion occurs in private companies, and establish what the position of the Public Accountant has been against evasion events of taxes in the exercise of his profession.